Competitiveness with sustainable agriculture: win, lose or draw? - Abdul Rahim, Khalid; Wong, Swee Kiong; Liwan, Audrey (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
Through the Polluter-Pays-Principle (PPP), it is generally assumed that the additional cost of internalization is passed on to consumers. However, stiff competition in the world market could make it difficult for exporters to pass on to international consumers, thus profit margin on export commodities is eroded and exports may be curtailed. This situation prevails in many developing countries which export a large proportion of their commodity production. When pollution control costs are substantial, voluntary implementation of environmental policy in the commodity export sector of a country may be problematic. Studies have shown mixed results that generalizations on the competitive effects of eco-friendly agriculture are unwise. Results of our study reveal that stricter environmental regulation to increase the cost of chemical inputs to encourage farmers to produce eco-friendly pepper products would enhance the export market competitiveness of both black pepper and white pepper production in Malaysia. On the other hand, to produce cocoa in a manner consistent with eco-friendly objectives requires huge sum of investment by the government. Each producer has different cost structure such that internalization of production externalities may result in higher cost of production for some countries but reduced cost for others. Cocoa growers in Brazil estimated an increased cost of 13.33% over variable costs at average productivity to compensate for adequate soil management, disease prevention and maintenance of production infrastructure. In Malaysia, one-third of the cost of production is accounted for the labour in combating the cocoa pod borers in estates in Sabah thus increasing the overall cost of production by 14%. However, evidence shows a reduction in the cost of production by 77% in Indonesia due to low wages in agriculture.